Whither financial regionalism among ASEAN+3 - Chin, Kok Fay (Penerbit UKM, 2011)
Having experienced a major crisis in 1997-98, several regional cooperative arrangements in finance were designed by ASEAN+3 to mobilize collective responses to cope with major financial crises. While the current global financial crisis poses a serious challenge to the adequacy of existing regional mechanisms and institutions for crisis prevention and management, it provides a good opportunity for ASEAN+3 countries to press for more legitimacy of the global financial arrangements. In the absence of an effective global solution, the West now place their hope in the key member states of the ASEAN+3 collective action to mitigate the severity of the impending global recession. Can ASEAN+3 rise to the expectation? In view of the magnitude of the crisis as well as weaknesses of the existing regional financial cooperation, it remains to be seen what impact the current global financial turmoil would have on financial regionalism between ASEAN and the ‘plus three’ countries - China, Japan and South Korea. Whether an effective global solution is emerging is the central issue and one which will determine the future direction of East Asian financial regionalism. This further raises the question of whether financial regionalism is still relevant. An attempt is made in this article to address these issues.